Konstruksi Nilai Ekologis pada Komitmen Perusahaan L’orèal dalam Iklan L’orèal Pour Le Futur - Selvia Nailas Sofa; Bernadus Wahyudi Joko Santoso (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2026)
The advertisement “L'Oréal pour le futur” is an advertisement aired by L'Oréal on YouTube with a nature theme. This study focuses on ecolinguistics analysis of the advertisement “L'Oréal pour le futur” using Charles Sanders Peirce's semiotics, which is the study of signs. Peirce identified a triadic relationship in semiotics. This study is a qualitative descriptive research. The purpose of this study is to identify the ecological elements in the advertisement that are interpreted semiotically according to Peirce's semiotics theory and to understand how the advertisement uses semiotics strategies to build a brand image that cares about the environment. Based on the analysis conducted using Peirce's trichotomy, signs were found in the advertisement that indicate L'Oréal's commitment and concern for the environment in its sustainable production process. This is evidenced by the commitment figures mentioned in the advertisement as steps the company will take, the use of production materials that prioritize environmentally friendly concepts, and concern for the energy sources used. Thus, from an ecolinguistics perspective, the advertisement “L’Oréal pour le futur” is an advertisement that contains ecological values from the company's commitment to its concern for sustainable environmental practices.